1991
DOI: 10.1183/09031936.93.04070829
|View full text |Cite
|
Sign up to set email alerts
|

What factors explain racial differences in lung volumes?

Abstract: In order to examine the physical characteristics that may determine racial differences in lung volumes, we studied healthy, nonsmoking Caucasian, Chinese and Indian males of similar ages (range 18-51 yrs). We measured spirometric function, flow volume curves, lung volumes, inspiratory and expiratory muscle pressures, alveolar distensibility and diffusing capacity, together with height, weight and fat free mass. Chest shape was measured using radiographs. The mean total lung capacity and vital capacity in the C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

1993
1993
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…However, if this effect alone accounted for swimmers' larger VC one would not anticipate an increase in the FRC seen in our swimmers, which is consistent with the possibility that swim training per se enhances lung growth. A previous study from this laboratory showed that Caucasians with higher values for MIPRv had values for alveolar distensibility similar to Indians and Chinese subjects with lower values for MIP RV [31]. This implies that an increased ability to distend the thoracic cage does not necessarily lead to an increased distensibility of the alveoli.…”
Section: Discussionmentioning
confidence: 81%
See 3 more Smart Citations
“…However, if this effect alone accounted for swimmers' larger VC one would not anticipate an increase in the FRC seen in our swimmers, which is consistent with the possibility that swim training per se enhances lung growth. A previous study from this laboratory showed that Caucasians with higher values for MIPRv had values for alveolar distensibility similar to Indians and Chinese subjects with lower values for MIP RV [31]. This implies that an increased ability to distend the thoracic cage does not necessarily lead to an increased distensibility of the alveoli.…”
Section: Discussionmentioning
confidence: 81%
“…adaptation alone. In a recent study [31], we reported lung volumes and chest dimensions in Chinese men closely approximating Caucasian values, and speculated that the next generation of Chinese will have similar lung capacities to Caucasians, probably as a result of better nutrition and more exercise.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…45 The difficulty in establishing the magnitude of differences between Caucasians and Africans or Asians accurately notwithstanding, it is certain that ethnicity is a major determinant of lung function. 46 Therefore, it is now a standard practice to develop separate equations for multi-ethnic populations. The most widely used equations in the United States are based on the NHANES III data.…”
Section: Ethnicitymentioning
confidence: 99%